LEGAL PROTECTION FOR PPAT FROM LAND MAFIA CRIME IN MAKING LAND DEEDS BASED ON PP 37 OF 1998 - Noor, Aslan; Purwa, Patriana (Sean Institute, 2023)
The land mafia is a serious threat to the sustainability of the land registration system and the legality of land ownership in Indonesia. One group that plays an important role in the process of making land deeds is the Land Deed Making Officer (PPAT). Therefore, legal protection for PPAT is very important to prevent land mafia crimes in making land deeds. This study aims to analyze how the legal protection for PPAT from land mafia crimes in making land deeds based on Government Regulation No. 37 of 1998. The research method used is qualitative research with a literature study approach. Data were analyzed using a descriptive-analytical approach. The results of the research show that existing regulations, especially Government Regulation Number 37 of 1998, provide a strong legal basis for PPATs in carrying out their duties in making land deeds. This regulation regulates the obligations, responsibilities and authorities of PPATs in carrying out their duties, as well as providing sanctions for PPATs who commit violations. However, the challenges faced in implementing these regulations were also encountered in this study. Some of the challenges faced include the lack of oversight of PPATs, low public legal literacy, and vulnerability to influence from the land mafia. In addition, legal practice and the role of the courts in providing legal protection for PPATs are still facing obstacles such as lengthy and complex legal processes, and the lack of effective sanctions against perpetrators of land mafia crimes. In maintaining the integrity and legality of land deeds made by PPAT, a synergy between regulations, legal practice and the courts is needed. Efforts to strengthen oversight of PPATs, increase public legal literacy, and increase the effectiveness of sanctions against land mafia perpetrators need serious attention. In addition, the role of the court in providing fair and prompt decisions in cases involving land mafia crimes is also important for enforcing the law and providing effective legal protection for PPATs and the public in making land deeds.